2022
DOI: 10.1021/acsapm.1c01634
|View full text |Cite
|
Sign up to set email alerts
|

Facile Processing of Polyelectrolyte Complexes for Immobilization of Heavy Metal Ions in Wastewater

Abstract: Practical application of polyelectrolyte complexes (PECs) has been limited due to inadequate techniques to overcome processing challenges. This study aimed to explore seamless PEC processing techniques to fabricate adsorbents for wastewater treatment. The phase transition associated with poly(diallyldimethylammonium) and poly(styrenesulfonate) complexes in an aqueous solvent was studied as a function of polymer concentration, charge stoichiometry, and ionic strength. The complex-to-coacervate and coacervate-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 67 publications
1
32
0
Order By: Relevance
“…Thus, the pseudo-second-order model is more reliable and accurate for describing the adsorption kinetics for Pb 2+ on CPCs900. These results are consistent with the kinetic model fitting results for pollutant-adsorbent systems reported in the literature. It has been reported that the adsorption conforming to the pseudo-second-order model is mainly chemical adsorption. , As such, Pb 2+ adsorption on CPCs900 could be dominated by chemical adsorption.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, the pseudo-second-order model is more reliable and accurate for describing the adsorption kinetics for Pb 2+ on CPCs900. These results are consistent with the kinetic model fitting results for pollutant-adsorbent systems reported in the literature. It has been reported that the adsorption conforming to the pseudo-second-order model is mainly chemical adsorption. , As such, Pb 2+ adsorption on CPCs900 could be dominated by chemical adsorption.…”
Section: Resultssupporting
confidence: 89%
“…We next explore the adsorption kinetics of Pb 2+ on CPCs900. Pseudo-first-order (eq ) and pseudo-second-order (eq ) models have been widely used for analyzing the adsorption kinetics of metal ions on solid materials. q e and q t are the amounts of metal ions adsorbed on adsorbent at equilibrium and at time t , respectively. k 1 (min –1 ) and k 2 (g mg –1 min –1 ) are rate constants of pseudo-first-order and pseudo-second-order models, respectively .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-sectional SEM image demonstrated the strong coupling between the cathode and SN-SPE without any discernible delamination ( Figure 8 b). As shown in Figure 8 c, the integrated ASSLIBs had smaller interface resistance than conventional ASSLIBs due to the better interface contact between electrode and electrolyte formed by in situ polymerization [ 104 ].…”
Section: In Situ Polymerization Methods For Gel Polymer Electrolytesmentioning
confidence: 99%
“…on the composition and properties of the coacervate and supernatant phases has emerged. 93 The crowded interiors of the coacervates and their ability to sequester charged (bio)macromolecules from their surroundings have promoted their utility as encapsulants and stabilizers in biological, 79,94 industrial, 95–97 environmental, 17,19,83 and cosmetic applications. 81,82…”
Section: Introductionmentioning
confidence: 99%